KU Leuven Fund for Fair Open Access - Mesotten, Laura; Verbeke, Demmy (Zenodo, 2018)
This poster was presented at the thirteenth Munin Conference on Scholarly Publishing held on 28 and 29 November 2018 in Tromsø, Norway. It discusses the KU Leuven Fund for Fair Open Access, which was established in March 2018 to provide financial support for fair OA monographs (BPCs), articles (APCs) and non-profit OA initiatives. The Fund only endorses non-profit gold OA that is in line with the principles of fair OA.The poster outlines the temporary findings and achievements of the Fund (March-October 2018).